Insights into ice-growth inhibition by trehalose and alginate oligosaccharides in peeled Pacific white shrimp (Litopenaeus vannamei) during frozen storage. (25th April 2019) - Zhang, Bin; Cao, Hui-juan; Lin, Hui-min; Deng, Shang-gui; Wu, Hao
Highlights: Saccharides slowed the damage caused to shrimp myofibrils by large ice crystals. Saccharides molecules were close to ice surface and embedded into ice layer. Hydrogen bonds interactions between ice surface and saccharides occurred. Saccharides suppressed growth of ice crystals and promoted solvation. Abstract: Cryoprotective saccharides are widely accepted antifreeze additives that reduce thawing loss, maintain texture, and retard protein denaturation in frozen seafood. In this study, the inhibition effects of trehalose and alginate oligosaccharides on ice growth were investigated and compared with sodium pyrophosphate (Na4 P2 O7 ) treatment in peeled shrimp during frozen storage, especially the interactions between saccharide molecules and ice crystals. The microstructural results demonstrated that the pre-soaking of trehalose and alginate oligosaccharides before freezing exhibited marked effects on stability of muscle tissue structures and slowed the damage caused to the myofibrils by large ice crystals. The ice-growth inhibition activities might play an important role in cryoprotective effects of saccharides on frozen muscle tissue. Furthermore, molecular docking and molecular dynamics (MD) simulations proved that saccharides were generally close to the ice interface and embedded in ice layers via hydrogen bonds or hydrophobic or electrostatic interactions. The saccharides–ice complex was partially destroyed, and some dislocation and disaggregation were observed around the saccharides molecules. Thus, the incorporated saccharides suppressed the growth of ice crystals, providing protection from freeze-induced damage. Here, the obtained structural details of the ice crystals interface affected by trehalose and alginate oligosaccharides were well in agreement with the histological (H&E staining) experimental results. These findings help better understand the ice-growth inhibition mechanisms of saccharides in frozen shrimp, and these two saccharides may be potentially used as ice-growth inhibitors in frozen seafood.